Fenomenologi Annemarie Schimmel: Telaah terhadap Kontribusi Annemarie Schimmel dalam Mengintegrasikan Normativitas dan Historisitas dalam Studi Islam Kontemporer - Hafidz, Abdul (Proceedings of Annual Conference for Muslim Scholars, 2019)
This article examines Annimarie Schimmel's phenomenological approach in an effort to integrate normativity and historicity approaches in Contemporary Islamic studies. The main problem in this study is there are tensions and the rise of counterproductive interpretations of the Orientalists toward Islam which is motivated by the partial use of historicality approach on the one hand and normative approaches to Muslims who tend to be textual. This study is a literature review with a historical approach and study of figures. Based on the discussions that have been carried out it can be concluded that the Annemarie Schimmel approach contributes in restoring the image of Islam in the West, being able to reconcile and create mutual understanding between the West and Muslims in understanding their respective religions and perceptions. In addition, being able to integrate, bridge and marry a normative and historical approach. Schimmel's phenomenology is applied by examining how to try to understand and enter the heart of a religion by examining the phenomenon first and then deeper and deeper layers of human response to God until he reaches the deepest sacred essence of each a religion, center, God or absconditus dues. While the model is the concentric ring model.